Experimental development and bond graph dynamic modelling of a brazed plate heat exchanger. (2017) - Kebdani, Mohamed; Dauphin-Tanguy, GeneviÁ¨ve; Dazin, Antoine; Dupont, Patrick
This article is devoted to the dynamic study of a brazed plate heat exchanger (BPHE). First, an introduction to the industrial context of the current FUI THERMOFLUIDE project is proposed. A succinct presentation of the heat exchanger technology is proposed. Afterward, a state of the art discussion of BPHE modelling, heat transfer and pressure drop correlations is given. Then a detailed mathematical description of an original dynamic model is presented. The last section deals with a description of the experimental test rig and performed validation tests.